Can Dietary Intake of Vitamin C-Oriented Foods Reduce the Risk of Osteoporosis, Fracture, and BMD Loss? Systematic Review With Meta-Analyses of Recent Studies - Zeng, Ling-Feng; Luo, Ming-Hui; Liang, Gui-Hong; Yang, Wei-Yi; Xiao, Xiao; Wei, Xu; Yu, Jie; Guo, Da; Chen, Hong-Yun; Pan, Jian-Ke; Huang, He-Tao; Liu, Qiang; et al. (Frontiers in Endocrinology, 2020)
Background: Several epidemiological studies have been performed to evaluate the association of dietary intake of vitamin C-oriented foods (DIVCF) with risk of fracture and bone mineral density (BMD) loss, but the results remain controversial. Therefore, we conducted a systematic meta-analysis to assess this correlation. Methods: We searched EmBase, PubMed, Web of Science, and the Chinese database CNKI for relevant articles published up to August 2019. Pooled relative risks (RRs) with 95% confidence intervals (CIs) were calculated using the random- or fixed-effects model. Discrepancies were resolved by consultation with a third expert. Results: A total of 13 eligible articles (including 17 studies) with 19,484 subjects were identified for the present meta-analysis. The pooled RR of hip fracture for the highest versus lowest category was 0.66 (95% CI, 0.47–0.94) for DIVCF, i.e., people with a greater frequency of Vitamin C uptake had a 34% (95% CI, 6%–53%) lower prevalence of hip fracture. In subgroup analyses stratified by study design, gender, and age, the negative associations were statistically significant. Furthermore, the statistical analysis of the association between DIVCF and risk of osteoporosis (RR, 0.66; 95% CI, 0.48–0.92), BMD at the lumbar spine (pooled r, 0.15; 95% CI, 0.09–0.23), and BMD at the femoral neck (pooled r, 0.20; 95% CI, 0.11–0.34) showed beneficial effects of DIVCF. Conclusion: Our meta-analysis indicates that DIVCF is negatively associated with the risk of hip fracture, osteoporosis, and BMD loss, suggesting that DIVCF decreases the risk of hip fracture, osteoporosis, and BMD loss.